Ù†Ù…ÙˆØ°Ø¬ Ø¨ÙŠØ¦Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥Ø±Ø´Ø§Ø¯ Ø³Ù…Ø§Ø±Ø§Ù†Ø¬ Ø¬Ø§ÙˆÙ‰ Ø§Ù„ÙˆØ³Ø·Ù‰ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ ÙˆØ¯ÙˆØ±Ù‡Ø§ ÙÙŠ Ø§ÙƒØªØ³Ø§Ø¨ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© - Said, Mochamad Munawar (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
The Arabic language is the language of the world that Muslims use. Every person must teach Arabic in schools and universities, even though they have obstacles and problems that interfere without reaching the desired legitimate goal. Teaching the Arabic language has many difficulties, including the language itself, society, teacher, and learner. This research aims to know the model of the Arabic language environment at the Guidance Institute Semarang Central Java and its role in acquiring language skills. The researcher is based on the descriptive study. The method of data collection was conducted in a way of observation, interview and documents. As for the way to analyze the data using a descriptive analysis that deals with description and focus. And its results are the integrated environment that combines the artificial environment with the natural environment. As for its role, it is to create the linguistic atmosphere in the places that are in the school and the residence so that the teacher can fix the linguistic mistakes made by students and deepen the repetition and strengthening of the language that they got from the school and the residence and encourage their spirit and enthusiasm in applying the language